TEACHER–PUPIL INTERACTION AS A FACTOR IN EFFECTIVE LEARNING IN PRIMARY EDUCATION (World Bulletin of Education and Learning, 2025)
Teacher–pupil interaction is a central component of effective learning in primary education, as it directly influences pupils’ cognitive development, motivation, emotional well-being, and academic achievement. In early schooling, learning is not limited to the transmission of knowledge but is shaped through continuous communication, feedback, and shared activity between teachers and pupils. This article examines teacher–pupil interaction as a significant pedagogical factor that determines the quality and effectiveness of learning in primary education. The study focuses on the educational value of positive, supportive, and dialogic interaction in the classroom and its role in creating a learner-centered environment. Special attention is given to the characteristics of effective interaction that correspond to the psychological and developmental needs of primary school pupils. The article argues that purposeful and well-organized teacher–pupil interaction enhances pupils’ engagement, supports the development of learning skills, and contributes to sustainable educational outcomes in primary education.
Keywords: teacher–pupil interaction, effective learning, primary education, classroom communication, pedagogical relationship